PENGARUH LAMA PENYIMPANAN ENTRES DAN PEMBERIAN KONSENTRASI BAP TERHADAP KEBERHASILAN SAMBUNG PUCUK TANAMAN LANGSAT - WATI, MURNA (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTThis study aimed to determine the effect success of storage duration and concentration of BAP on the of Lansium shoot grafting. This research was conducted in Sungai Belidak Village, Sungai Kakap Subdistrict, Kubu Raya Regency on 13 June - 13 September 2018. The method used in this study was a field experiment method with a completely randomized design (CRD), which consisted of 2 treatment factors, i.e.: treatment duration of storage and concentration of BAP,in which, each factor consists of 3 treatment combinations, namely: l0b0 (entres without being stored and without soaking BAP) l01 (entres without stored and soaked in 50 ppm BAP) lb2 (entres without being stored and soaked in 100 ppm BAP) 1b0 (entress stored for 6 hours and without soaking BAP) l1b1 (entres stored for 6 hours and soaked in 50 ppm BAP) l1b2 (entres stored for 6 hours and soaked in 100 ppm BAP) l2b0 (entres stored for 12 hours and without soaking BAP) l2b1 (entres stored for 12 hours and soaked BAP 50 ppm) l2b2 (entres stored 12 hours and soaked BAP 100 ppm). Each treatment consisted of 3 replications and each replication consists of 5 plant samples, so that a total of 135 plants were obtained. The variables observed consisted of: percentage of graft success (%), number of leaves formed (leaves), increase of entres length (cm), time of shoots emergence (days), number of shoots emerged (shoots), time of leaf fall (days) and number fallen leaves (leaves).The results showed that the treatment duration of entres storage and BAP concentrations had no significant effect on the observation variable, except for the leaves fall (days) which showed a significant effect on the observed variable.Keywords: BAP Concentration, Entres Storage, Lansium, shoot grafting